2013
DOI: 10.1074/jbc.m113.464792
|View full text |Cite|
|
Sign up to set email alerts
|

Mice Lacking α-Tubulin Acetyltransferase 1 Are Viable but Display α-Tubulin Acetylation Deficiency and Dentate Gyrus Distortion

Abstract: Background: Biological functions of mammalian Atat1 and its contribution to ␣-tubulin acetylation in vivo remain elusive. Results: Atat1-null mice are viable but possess deficient ␣-tubulin acetylation and a bulge in the dentate gyrus. Conclusion: Mouse Atat1 is a predominant ␣-tubulin acetyltransferase in vivo and fine-tunes hippocampus development. Significance: Mammalian Atat1 is not required for survival and development but may regulate more advanced functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 84 publications
(129 reference statements)
9
102
2
Order By: Relevance
“…In agreement with recent work (Kalebic et al. , 2013b; Kim et al. , 2013), no acetylated tubulin was detected in the αTat1-deficient mouse brain, either by immunoblot or immunohistochemistry, suggesting that αTat1 is the sole tubulin acetyltransferase in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with recent work (Kalebic et al. , 2013b; Kim et al. , 2013), no acetylated tubulin was detected in the αTat1-deficient mouse brain, either by immunoblot or immunohistochemistry, suggesting that αTat1 is the sole tubulin acetyltransferase in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, αTAT1 associates with acetylated MTs in axons and cilia in vivo [65, 66]. Indeed, male mice lacking αTAT1 are less fertile due to altered sperm morphology and motility [65]; however, they do not exhibit obvious behavioral or neurological defects beyond subtle changes in brain architecture [70]. However, in mice without αTAT1 or acetylated MTs, the MTs were more resistant to nocodazole, suggesting increased MT stability [65].…”
Section: Acetylation and Deacetylation Of Tubulinsmentioning
confidence: 99%
“…However, other studies have shown that αTat1 (α-tubulin K40 acetyltransferase) is a predominant/major α-tubulin acetyltransferases in vivo in mammals and nematodes and fine-tunes hippocampus development (Shida et al, 2010; Kim et al, 2013). As a side note, in D. melanogaster , Naa50 has been shown to acetylate β-tubulin at K252 on soluble tubulin heterodimers but not tubulins in MTs.…”
Section: Mammalsmentioning
confidence: 99%